Transformações estruturais e evolução da produtividade total dos fatores da agropecuária paranaense no período de 1970 a 2004 : um estudo na Associação dos Municípios do Setentrião Paranaense AMUSEP - Franco, Juliana (2006)
From the 1970 decade, the Brazilian farming sector faced a modernization process, resulting structural transformations in the productive process and significant productivity gains. In this way, this paper analyzed the transformations at Paraná farming and at the Setentrião Paranaense Cities Association (AMUSEP) from 1970 till 2004, attempting to investigate the main changes concerning the products and inputs composition in the productive process and the total and partial productivity evolution of the production factors. Therefore, structural change indicators has been constructed: Specialization, Factors Total Productivity by Tornqvist method, and Land-Work Partial productivity indicator. The research results had evidenced that the Brazilian farming modernization brought a generalized process of transformations in the paranaense farming and in the AMUSEP cities, that was expressed by the significant Factors total and partial productivity gains and by structural change indicators. However, in this period, the sector had structuralized and modernized facing with dynamism the subsequent years adverse factors. Thus, this modernization effects and the structural transformations in the farming remained after 1990, being verified in the Production Factors Total and Partial Productivity continuous gains, however by decreasing taxes.